Breaking Barriers, Building Bridges: An Indigenized Nursing Admissions Process. - Llanque-White, Sarah M.; Kahn-John, Michelle; Matt, Aretha (International Journal for Human Caring, 2025)
The representation of American Indian and Alaska Native (AIAN) nurses is critically low, with 1% of the registered nurse workforce identifying as AIAN. Systemic barriers, including inequities in K-12 education and culturally misaligned admissions criteria, hinder access to nursing education for AIAN students. This article presents an innovative effort at Navajo Technical University to Indigenize nursing admissions and curricula following the 2025 reopening of its Associate of Applied Science Registered Nurse Program. Rooted in the Diné (Navajo) Philosophy of Education and the Hózhó framework, the program adopted a holistic admission process that evaluates applicants based on caregiving experience, cultural knowledge, resilience, and community commitment, rather than just grades or test scores. This shift resulted in the successful admission of 10 Indigenous students, compared with none previously. By integrating Indigenous worldviews into admissions and curriculum design, this approach promotes inclusivity, validates Indigenous knowledge, and aims to enhance diversity in the nursing workforce while advancing health equity for Indigenous populations.